Embedding Automated Writing Evaluation in Providing Formative Feedback - Defianty, Maya; Zulfa, Siti; Mulyati, Yatni Fatwa (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
The pivotal role of feedback in improving students’ writing competence has been undeniable, yet there has not been any agreement about how feedback can improve learning. The advancement of technology has opened opportunities to give feedback facilitated by technology, commonly referred to as Automated Writing Evaluation (AWE). AWE-based applications help produce effective feedback mostly because they are friendly. Several studies have documented that several AWE-based applications can potentially improve students’ writing skills. Nevertheless, effective feedback constitutes more than timely feedback. AWE-based applications cannot attain other factors, such as ongoing and goal-oriented. In other words, an AWE-based application is merely a form of feedback, such as comments and scores. Therefore, improving students’ writing competence cannot rely solely on AWE-based applications. The AWE-based application should be framed in the process of feedback provision that aims to improve learning, known as formative feedback. This paper elaborates on how AWE can be framed in formative feedback. The concept of formative feedback and the writing process will be discussed thoroughly before discussing how AWE tools can be embedded in formative feedback during the writing process.